Female-voice song and women's musical agency in the middle ages - Grau, Anna Kathryn; Colton, Lisa (Brill's companions to the musical culture of medieval and early modern Europe, 2022)
Intro -- Contents -- Acknowledgements -- Figures, Tables and Music Examples -- Figures -- Tables -- Music Examples -- Notes on Contributors -- Introduction: Female Authorship, Female Voice, and Female-Voice Song -- 1 Medieval Women's Song and the Authorship Question -- 2 Overview of chapters -- Bibliography -- Part 1: Ritual Discourse -- 1. The Feminine Voice in the Early Islamicate Courts (661-1000) -- 1 Sources and Methodology -- 2 Musicians, Gender, and Status in the Early Islamicate Courts -- 3 The Sound of Song -- 4 ᶜArīb al-Ma'mūniyya -- 5 Ṭuways -- 6 Some Conclusions -- Bibliography -- Primary sources -- Secondary sources -- 2. Music, Liturgy, and the Discursive Construction of Gender in a Thirteenth-Century Double -- 1 Liturgy and Gender as Performance -- 2 The Medieval Case For and Against Double Monasteries -- 3 Relationships and Interactions in Engelberg -- 4 Music and Gendered Relationships -- 5 A Series of Song of Songs Antiphons -- 6 Conclusion -- Bibliography -- 3. A Female-Voice Ceremonial from Medieval Castile -- 1 A Problematic Affiliation to Cîteaux -- 2 The Nuns' Public Visibility -- 3 The Las Huelgas Ceremonial -- 4 Female-Voice Liturgical Regulations -- 5 Hu 11 in Light of Hu 6 -- Bibliography -- 4. Religious Reform and Liturgical Change in the Fifteenth Century: Chant as Women's Protest Music -- 1 The Judas Psalm and Women's Understanding of Scripture -- 2 Women, Liturgy, and Fifteenth-Century Reform -- 3 The Judas Responsory and Women's Liturgical Agency -- 4 Conclusion -- Bibliography -- Manuscripts -- Primary Sources -- Secondary Sources -- Part 2: Materiality -- 5. Beyond this Mist: Uncovering Material Multiplicities in Amis, amis -- 1 Manuscript, Materiality, and Evanescence -- 2 Voice and Gender -- 3 Women, Devotion, and Desire -- 4 Finding Melody: Fragmentation and Transcription -- 5 Incarnations.